PENERAPAN METODE EKSPERIMEN FISIKA UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS DAN KREATIF - Sunarsih Sunarsih (Ideguru: Jurnal Karya Ilmiah Guru, 2020)
This classroom action research aims firstly is to determine the feasibility of learning by using the physics experimental method, secondly is to improve the critical and creative thinking skills of students of class X MM1 at SMK Negeri 1 Bantul, to improve learning outcomes of class X MM1 students at SMK Negeri 1 Bantul. This research data collection technique using observation, evaluation, field notes, and documentation. This research is a Classroom Action Research (CAR) which has 2 (two) cycles through 4 (four) stages starting from planning, implementing, observing and reflecting. The subjects of this study was 31 students of class X MM1 SMK Negeri 1 Bantul in the academic year of 2018/2019. The results of the study showed that the application of the physics experimental method was able to improve students' critical and creative thinking skills in class X MM1 SMK Negeri 1 Bantul in the 2018/2019 academic year. This is evidenced by the increase in value in the research instrument. In the student observation sheet, the shown 57.18 it was obtained with the criteria lacking at the initial observation stage, in the first cycle the value increased to 60.16 and in the second cycle the value was 69.56. In addition, classical completeness in the evaluation of learning outcomes also increased, at the initial evaluation classical completeness was 35.48%, in cycle I increased to 51.61% and in cycle II classical completeness became 77.42%.